2022
DOI: 10.1088/1555-6611/ac5b74
|View full text |Cite
|
Sign up to set email alerts
|

Tight focusing of high-order polarized anomalous vortex beam

Abstract: Based on the vector Debye theory, the tight focusing properties of a high-order polarized anomalous vortex (HPAV) beam are studied. The corresponding mathematical expressions of the HPAV beam are derived theoretically. We accomplish the inner and outer gear shapes of the focusing intensity where the number of the gear tooth can be modulated by polarization order. The results show that the focusing gear intensity can be flexibly modulated by initial polarization azimuth which may determine the trapping effects.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…where A is a constant, m represents the topological charge and n is the beam order, ω 0 is the beam waist (m = n = 0) of Gaussian beam, r and ϕ are the radial and angular coordinates of cylindrical reference respectively, and Q p,m (r, ϕ, θ) is the polarization matrix [17]. Shown in Fig.…”
Section: B Focusing Of Higher-order Vector Beammentioning
confidence: 99%
See 1 more Smart Citation
“…where A is a constant, m represents the topological charge and n is the beam order, ω 0 is the beam waist (m = n = 0) of Gaussian beam, r and ϕ are the radial and angular coordinates of cylindrical reference respectively, and Q p,m (r, ϕ, θ) is the polarization matrix [17]. Shown in Fig.…”
Section: B Focusing Of Higher-order Vector Beammentioning
confidence: 99%
“…The higher-order vector beam be produced based on laser resonators and multi-beam interference, but these methods are only applicable for lower-order vector beam as the setup for higher-order vector beam is complex [6], [15], [16]. One of the significant applications of higherorder vector beam is high-resolution imaging; Xu et al [17] reported that higher-order vector beam can focus into a circular spot with high resolution when the polarization order p equals the topological charger m. However, only analytical results were given therein; in the tight focusing case, there may be non-negligible difference between analytical and practical results. Therefore, an approach of compact setup that is experimentally simple and is applicable to generating higher-order vector beam of arbitraryorder remains elusive.…”
Section: Introductionmentioning
confidence: 99%